Study on microscopic pore structures and mechanical properties - Shihu ZHAO; Yong LI; Yali LIU; Yanbin WANG; Zengqin LIU; Gang CHEN; Xinjun CHEN (Shiyou shiyan dizhi)
The pore structures and mechanical properties of coal are key parameters for geological evaluation of coalbed methane, reflecting its reservoir capacity and compressibility. The study investigated four coal samples from the Qinshui and Datong basins in Shanxi Province, including Jurassic coal from Datong (Ro=0.91%), No. 2 coal from the Shanxi Formation in Gujiao (Ro=1.34%), No. 8 coal of the Taiyuan Formation in Gujiao (Ro=1.70%), and No. 2 coal of the Shanxi Formation in Yicheng (Ro=1.77%). Using atomic force microscopy (AFM), a combined characterization technique was established for microscopic pore structure and mechanical properties based on image segmentation and Derjaguin-Muller-Toporov (DMT) mechanical model. This method clarified the microscopic pore structure and mechanical properties of coal samples and revealed the influence of material composition, pore structure, and thermal evolution level on their microscopic mechanical properties. The results showed that the surface porosity of coal samples mainly ranged from 2.72% to 4.60%, with an average of 3.58%. The total pore surface area and total pore volume were (3.413-5.638)×10-2 μm2/μm2 and (0.5-3.9)×10-4 μm3/μm2, respectively. The pore sizes were mainly distributed between 10-100 nm, and the Young's modulus ranged from 2.24 to 3.10 GPa, with an average of 2.77 GPa. The mechanical properties of coal were influenced by the material composition, pore structure, and thermal evolution level. As moisture decreased and volatile and mineral content increased, the Young's modulus showed an increasing trend. With an increase in surface roughness, mean pore size, porosity surface, specific surface area, and total pore volume, the Young's modulus decreased. As thermal evolution progressed, the Young's modulus decreased. AFM enables simultaneous analysis of microscopic pore structure and mechanical properties of coal, providing new methods and insights for studying reservoir capacity and mechanical behavior of coal reservoirs. It holds significant implications for the evaluation of reservoir capacity and compressibility in unconventional reservoirs.